The Effect of an Educational and Interactive Informed Consent Process on Patients With Cervical Spondylotic Myelopathy Caused by Ossification of the Posterior Longitudinal Ligament. Issue 3 (1st February 2020) - Lee, Young-Seok; Cho, Dae-Chul; Sung, Joo-Kyung; Han, Inbo; Kim, Chi Heon; Kim, Ji-Yoon; Kim, Kyoung-Tae
Abstract : Study Design: Prospective observational cohort study. Objective: In this study, an educational and interactive informed consent (EIC) program was proposed for patients with cervical spondylotic myelopathy caused by ossification of the posterior longitudinal ligament (OPLL-CSM) to improve their comprehension level during the informed consent process. Summary of Background Data: OPLL-CSM is a slow progressive disease, and it is difficult for patients to understand the disease. Few studies have evaluated very specific programs to improve the informed consent process for these patients. Methods: This prospective study evaluated patients with OPLL-CSM who either underwent the proposed EIC process (n = 63) or the standard consent process (n = 124). The standard consent process only included a physician–patient interview. During the EIC process, information was provided regarding OPLL-CSM through information booklets, a video, verbal information, and initial and second physician–patient interviews. After the second physician–patient interview, the patient was requested to answer 14 medical questions to assess their knowledge about OPLL-CSM. The proposed EIC process took approximately 90 minutes. They were asked to report the most useful educational method and the most effective method of reinforcing verbal communication. Results: The mean questionnaire scores were higher in the EIC group than in the control group ( P  < 0.001). Video was selected by 50/63 patients (79.4%) as the most useful EIC process method, and the most effective method of reinforcing verbal communication was video (n = 61; 96.8%). Patients in the EIC group reported having higher satisfaction with surgery ( P  = 0.024) than did those in the control group. Conclusion: The proposed EIC process was shown to result in good patient comprehension and recall regarding OPLL-CSM. Using a video was the most informative and effective reinforcement of verbal communication. The enhanced educational group had better knowledge and improved satisfaction following surgery. The EIC process might help physicians educate and counsel patients regarding OPLL-CSM and its treatment. Level of Evidence: 2 Abstract : Supplemental Digital Content is available in the textThe proposed an educational and interactive informed consent (EIC) process performed an initial physician–patient interview using information booklets and video and a second interview for reinforcement. The proposed EIC process was shown to result in good patient comprehension. The video was the most informative and effective reinforcement.